Increased Interleukin 18-Dependent Immune Responses Are Associated With Myopericarditis After COVID-19 mRNA Vaccination - Won, Taejoon; Gilotra, Nisha Aggarwal; Wood, Megan Kay; Hughes, David Matthew; Talor, Monica Vladut; Lovell, Jana; Milstone, Aaron Michael; Steenbergen, Charles; Čiháková, Daniela (Frontiers in Immunology, 2022)
Myocarditis and myopericarditis may occur after COVID-19 vaccination with an incidence of two to twenty cases per 100,000 individuals, but underlying mechanisms related to disease onset and progression remain unclear. Here, we report a case of myopericarditis following the first dose of the mRNA-1273 COVID-19 vaccine in a young man who had a history of mild COVID-19 three months before vaccination. The patient presented with chest pain, elevated troponin I level, and electrocardiogram abnormality. His endomyocardial biopsy revealed diffuse CD68+ cell infiltration. We characterized the immune profile of the patient using multiplex cytokine assay and flow cytometry analysis. Sex-matched vaccinated individuals and healthy individuals were used as controls. IL-18 and IL-27, Th1-type cytokines, were highly increased in the patient with COVID-19 vaccine-related myopericarditis compared with vaccinated controls who experienced no cardiac complications. In the patient, circulating NK cells and T cells showed an activated phenotype and mRNA profile, and monocytes expressed increased levels of IL-18 and its upstream NLRP3 inflammasome. We found that recombinant IL-18 administration into mice caused mild cardiac dysfunction and activation of NK cells and T cells in the hearts, similar to the findings in the patient with myopericarditis after COVID-19 mRNA vaccination. Collectively, myopericarditis following COVID-19 mRNA vaccination may be associated with increased IL-18-mediated immune responses and cardiotoxicity.